2020
DOI: 10.1016/s0140-6736(20)31029-1
|View full text |Cite
|
Sign up to set email alerts
|

Consider pregnancy in COVID-19 therapeutic drug and vaccine trials

Abstract: Consider pregnancy in COVID-19 therapeutic drug and vaccine trials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 3 publications
0
90
0
5
Order By: Relevance
“…Pregnant women are highly vulnerable to emerging diseases such as COVID-19 due to alterations in the immune system and other physiological systems that are associated with pregnancy. Therefore, in the event of successful vaccine development, pregnant women will not get access to the vaccines ( 361 ). Hence, it is recommended that pregnant women be included in the ongoing vaccine trials, since successful vaccination in pregnancy will protect the mother, fetus, and newborn.…”
Section: Vaccines Therapeutics and Drugsmentioning
confidence: 99%
“…Pregnant women are highly vulnerable to emerging diseases such as COVID-19 due to alterations in the immune system and other physiological systems that are associated with pregnancy. Therefore, in the event of successful vaccine development, pregnant women will not get access to the vaccines ( 361 ). Hence, it is recommended that pregnant women be included in the ongoing vaccine trials, since successful vaccination in pregnancy will protect the mother, fetus, and newborn.…”
Section: Vaccines Therapeutics and Drugsmentioning
confidence: 99%
“…Testing treatments is problematic because pregnant women are excluded from most trials. 254 It is known that azithromycin doubles innate IFN production from virus-infected lung cells. 255 It is safe for all trimesters of pregnancy 256 and has been shown effective in highquality clinical trials of virus-induced lung disease.…”
Section: Are There Specific Treatments For Pregnant Women In Case Omentioning
confidence: 99%
“…For policymakers to make informed decisions about immunisation programmes, reliable data are essential. It is therefore vital that pregnant women are included in immunisation trials, yet they are often systematically excluded ( 77 ). A recent media report suggested that the first two COVID-19 vaccines to enter large-scale testing in the US will not include pregnant women ( 78 ), similarly pregnant women or those planning to become pregnant are currently excluded from both national vaccine trials in the UK ( 79 ).…”
Section: Lessons Learnedmentioning
confidence: 99%